Study for Optimal Energy Management System in Houses Collectively Receiving Electricity at Low Voltage. (December 2017) - Nishiura, Eiji; Matsuhashi, Ryuji
Abstract: Currently collective electricity receiving and its trade among houses are promoted as a method of energy saving. Previous researches investigated the possibility of collective receiving of high voltage electric power. In this research, we evaluate collective electricity receiving at low voltage and its trade among houses with photovoltaics and fuel cells. In this system, power receiving facility for high voltage is not necessary, although the price of electricity is higher. We develop a Mixed Integer Non-Linear Problem (MINLP) model of the system, introducing the wheeling rate as a benefit of the aggregator. Then we adopted the concept of Nucleolus in game theory to maximize the minimum benefit of all houses. By doing this, we design a system that distributes profits fairly among house.